2022
DOI: 10.3389/fpubh.2022.1010194
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sleep quality and life satisfaction in adolescents: A cross-sectional survey study

Abstract: BackgroundPhysical activity, sleep is an important component of adolescents' 24-h movement behavior, and life satisfaction predicts adolescent physical and mental health. However, few studies have explored the relationship between the two variables among Chinese high school students. Consequently, this study aimed to explore the relationship between sleep quality and life satisfaction among Chinese high school students.MethodsThis cross-sectional study was conducted in October 2020 in five high schools in Xuch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The exercise intervention also increased sleep quality in subjective sleep assessment using VAS. The effectiveness of physical activity as one of the preventive measures for insomnia and sleep disorders has been reported in previous studies [ 29 , 30 ]. Inoue et al [ 31 ] conducted a 2-year longitudinal study of 3679 community-dwelling elderly people to examine the association between exercise habits and sleep, and found that those who exercised at least 5 days per week were less likely to experience mid-wake, one of the symptoms of insomnia, than those who did not exercise, indicating that habitual exercise may help control insomnia symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…The exercise intervention also increased sleep quality in subjective sleep assessment using VAS. The effectiveness of physical activity as one of the preventive measures for insomnia and sleep disorders has been reported in previous studies [ 29 , 30 ]. Inoue et al [ 31 ] conducted a 2-year longitudinal study of 3679 community-dwelling elderly people to examine the association between exercise habits and sleep, and found that those who exercised at least 5 days per week were less likely to experience mid-wake, one of the symptoms of insomnia, than those who did not exercise, indicating that habitual exercise may help control insomnia symptoms.…”
Section: Discussionmentioning
confidence: 87%